READING READINESS TEST FOR KINDERGARTEN CHILDREN (Sains Humanika, 2008)
Learning to read is an on–going developmental process and readiness is just a concept in the various stages of learning to read. Reading readiness is often referred as the earliest stage of informal reading skills that involve young children. It is the basic common traits which would help a child to begin his academic endeavour without much difficulties. To study the ability of cognitive aspect on reading, a reading readiness test in bahasa Melayu was developed. This test consists of six aspects, namely visual discrimination, phonological awareness, letter and letter–sound relationship, aural cloze with letter, sight words, and listening comprehension. This test was given to 130 kindergarten children randomly selected from six kindergartens to determine its psychometric stability. A test–retest analysis shows that the test has a fairly high reliability of more than 0.80, hence suggests its pragmatic utility. It is hoped that the test would enable kindergarten authority in identifying students who need special attention in their learning process, specifically in reading.
Keywords: Readiness; reading readiness; reading readiness test